Mesoporous silica nanoparticles in target drug delivery system: A review - Bharti, Charu; Nagaich, Upendra; Kumar Pal, Ashok; Gulati, Neha (International Journal of Pharmaceutical Investigation)
Due to lack of specifi cation and solubility of drug molecules, patients have to take high doses of the drug to achieve the desired therapeutic effects for the treatment of diseases. To solve these problems, there are various drug carriers present in the pharmaceuticals, which can used to deliver therapeutic agents to the target site in the body. Mesoporous silica materials become known as a promising candidate that can overcome above problems and produce effects in a controllable and sustainable manner. In particular, mesoporous silica nanoparticles (MSNs) are widely used as a delivery reagent because silica possesses favorable chemical properties, thermal stability, and biocompatibility. The unique mesoporous structure of silica facilitates effective loading of drugs and their subsequent controlled release of the target site. The properties of mesoporous, including pore size, high drug loading, and porosity as well as the surface properties, can be altered depending on additives used to prepare MSNs. Active surface enables functionalization to changed surface properties and link therapeutic molecules. They are used as widely in the fi eld of diagnosis, target drug delivery, bio-sensing, cellular uptake, etc., in the bio-medical fi eld. This review aims to present the state of knowledge of silica containing mesoporous nanoparticles and specifi c application in various biomedical fi elds.
Keywords: Bio-distribution; evaporation-induced self-assembly; mesoporous silica nanoparticles; silica precursors; surface functionalization; target drug delivery